The Significant Effects of Agricultural Systems on The Environment - Kaleem Ullah, Muhammad; Shabir, Sana (Journal of World Science, 2023)
The sustainability of our world and the ecological balance are significantly shaped by agricultural systems. The main environmental implications of agricultural practices are highlighted in this research with an emphasis on both the detrimental effects and proposed remedies to lessen these effects. By supplying food, fiber, and different raw materials, agricultural systems are essential for maintaining human populations. These systems, though, have the potential to have a significant negative or positive impact on the environment. An overview of the main environmental impacts of agricultural systems is given in this research First, agricultural systems play a significant role in the production of greenhouse gases. The release of carbon dioxide (CO2), methane (CH4), and element oxide (N2O), all of which are powerful greenhouse gases that contribute to climate change, is influenced using synthetic fertilizers, intensive livestock production, and changes in land use. Second, agricultural practices have an impact on water resources. The overuse of irrigation water can cause groundwater aquifers to be depleted and rivers and lakes to dry up. Additionally, the fertilizer and pesticide-contaminated runoff from agricultural fields can contaminate water sources, leading to eutrophication and harming aquatic ecosystems. Adopting sustainable agricultural practices is necessary to meet rising food demands while reducing adverse effects. These methods include organic farming, agroforestry, precision agriculture, and improved water management strategies. By putting such practices into practice, one can encourage a more resilient and sustainable food production system while also reducing the negative environmental effects of agriculture.